Network competition in nonlinear pricing - Dessein, Wouter (online, 2000)
Abstract:
urn:nbn:de:0168-ssoar-116294
Keywords: (stw)Telekommunikation; (stw)Preiswettbewerb; (stw)Preismanagement; (stw)Markteintritt; (stw)Netzregulierung; (stw)Wettbewerbspolitik; (stw)Theorie; (thesoz)Telefon; (thesoz)Telekommunikation; (thesoz)Gebühr; (thesoz)Preispolitik; (thesoz)Preisbildung; (thesoz)Markterschließung; (thesoz)Wettbewerb; (thesoz)Nachfrage; Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Als Aufsatz endgültig erschienen; Telekommunikation; Fernmeldewesen; Telekommunikationswirtschaft; Preiswettbewerb; Preispolitik; Markteintrittsstrategie; Netzzugang; Wettbewerbspolitik; Theorie